Serum Progesterone Level on the Day of Embryo Transfer Is Not a Reliable Predictor for Frozen–Thawed Embryo Transfer Outcomes With Euploid Blastocyst Transfer: A Retrospective Cohort Study - Chen, Wenjun; Xu, Yiyao; Liu, Xinyan; Pan, Jiafu; Cai, Bing; Zhou, Canquan; Xu, Yanwen; Gu, Fang (BJOG : an international journal of obstetrics and gynaecology, 2025)
ABSTRACT Objective To investigate whether serum progesterone (P4) levels on embryo transfer (ET) day correlate with the likelihood of live birth in artificial frozen–thawed transfer cycles using intramuscular progesterone. Design Retrospective cohort study. Setting University‐affiliated hospital. Population Patients undergoing single euploid blastocyst transfer after preimplantation genetic testing. Methods Live birth rate (LBR) was calculated in each percentile of serum P4 to detect a threshold associated with an increased probability of LB. The association between serum P4 and pregnancy outcomes was evaluated using multivariable logistic regression analysis. Main Outcome Measures LBR was the primary outcome. Secondary outcomes included clinical pregnancy rate (CPR) and early pregnancy loss (EPL) rate. Results In total, 761 patients were included, and the overall LBR was 55.72%. For LBR, each percentile group of serum P4 did not significantly differ. The distributions of P4 were comparable between the LB and non‐LB groups, with an average of 12.62 ± 4.05 and 12.84 ± 4.39 ng/mL, respectively. The multivariate analysis revealed that serum P4 did not affect the LBR, whereas the day of the blastocyst (D5 vs. D6: adjusted odds ratio [aOR] 2.15, 95% confidence interval [CI] 1.52–3.03) and embryo quality (good vs. viable embryo: aOR 1.88, 95% CI 1.37–2.58) were independently associated with LBR. Similarly, serum P4 was not associated with CPR and EPL rates. Conclusions Serum P4 levels on ET day do not predict LBR in artificial cycles with intramuscular progesterone.